2021
DOI: 10.5858/arpa.2021-0296-sa
|View full text |Cite
|
Sign up to set email alerts
|

Hofbauer Cells and COVID-19 in Pregnancy

Abstract: Context.– Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can undergo maternal-fetal transmission, heightening interest in the placental pathology findings from this infection. Transplacental SARS-CoV-2 transmission is typically accompanied by chronic histiocytic intervillositis together with necrosis and positivity of syncytiotrophoblast for SARSCoV-2. Hofbauer cells are placental macrophages that have been involved in viral diseases including HIV and Zika virus, but their involvement in SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 70 publications
(96 reference statements)
5
39
0
Order By: Relevance
“…In this placenta, the syncytiotrophoblast was also positive using both immunohistochemical and RNA in situ hybridization methods, but Hofbauer cell and villous capillary endothelial staining was not present. This observation is interesting in view of the recent demonstration by Schwartz et al [29] that among 22 placentas infected with SARS-CoV-2, four (18%) placentas had positive staining of Hofbauer cells and two (9%) placentas demonstrated staining of villous capillary endothelial cells for the virus. Because the syncytiotrophoblast and cytotrophoblast are in intimate physical contact with one another, and the villous cytotrophoblast has been demonstrated to stain using antibody to the ACE2 receptor protein [52,53], it appears likely that our observation of the simultaneous presence of SARS-CoV-2 antigen and nucleic acid in both cell types indicates cell-to-cell passage of the virus.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In this placenta, the syncytiotrophoblast was also positive using both immunohistochemical and RNA in situ hybridization methods, but Hofbauer cell and villous capillary endothelial staining was not present. This observation is interesting in view of the recent demonstration by Schwartz et al [29] that among 22 placentas infected with SARS-CoV-2, four (18%) placentas had positive staining of Hofbauer cells and two (9%) placentas demonstrated staining of villous capillary endothelial cells for the virus. Because the syncytiotrophoblast and cytotrophoblast are in intimate physical contact with one another, and the villous cytotrophoblast has been demonstrated to stain using antibody to the ACE2 receptor protein [52,53], it appears likely that our observation of the simultaneous presence of SARS-CoV-2 antigen and nucleic acid in both cell types indicates cell-to-cell passage of the virus.…”
Section: Discussionmentioning
confidence: 54%
“…However, there are data suggesting that term placentas from pregnant women infected with SARS-CoV-2 have increased levels of the ACE2 protein [48]. In addition to the syncytiotrophoblast, small numbers of infected placentas have been found to demonstrate positive immunohistochemical staining for SARS-CoV-2 in other fetal-derived placental cells including Hofbauer cells and villous capillary endothelial cells [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pronounced inflammation due to SARS-CoV-2 has also been reported in two at-term placentas, both at the cytokine and at the genetic level (21). Placental SARS CoV-2 infectionas demonstrated e.g., by systematic investigation of 22 SARS CoV-2 positive placentas (22)-is consistently associated with chronic histiocytic intervillositis, trophoblast necrosis (22)(23)(24) and it is frequently accompanied by fibrin depositions (23,25). These findings-chronic histiocytic intervillositis and trophoblast necrosis-were shown in both liveborn and stillborn neonates infected by transplacental transmission (24).…”
Section: Placental Inflammation By Sars-cov-2mentioning
confidence: 92%
“…It should also be noted that the extensive placental damage induced by SARS CoV-2 has caused pathologists to be concerned about potential neurologic sequelae in affected children (25). Schwartz et al further showed that Hofbauer cell positivity is not required for transplacental fetal infections (22). Another group found that maternal clinical COVID-19 symptoms did not predict the severity of the SARS-CoV-2related placental signature (26).…”
Section: Placental Inflammation By Sars-cov-2mentioning
confidence: 99%